Compressive strength of blended Portland cement mortars incorporating fly ash and silica fume at high volume replacement - Wongkeo W. (2014)
Fly ash has been widely used as a replacement of Portland cement at high content levels, but the compressive strength of Portland cement blended with fly ash is lower at early ages. Thus, this study compares the compressive strength of ternary blended Portland cement mortars incorporating fly ash (40-70 wt%) and silica fume (5-10 wt%) with binary blended Portland cement mortars incorporating fly ash only. Blended Portland cement mortars were designed with a constant water/binder ratio of 0.485 and the flow table tested was carried out. A fine aggregate to binder ratio of 2.75 was used. The compressive strength of all blended Portland cement mortars that cured in water at 23 °C was tested at 28 days. The results show that the flow of blended Portland cement mortars increased with increasing fly ash content and tended to decrease with increasing silica fume content, at the same replacement level. Moreover, the compressive strength of blended Portland cement mortars decreased with increasing fly ash content. However, compressive strength gains were obtained from ternary blended Portland cement mortars incorporating silica fume, tending to increase with increasing silica fume content.